Direct Conversion of Liquid Organic Precursor into 3D Laser‐Induced Graphene Materials. Issue 9 (30th December 2022) - Yu, Wenjie; Zhao, Weiwei; Wang, Shuaipeng; Chen, Qing; Liu, Xiaoqing
Abstract: Among the different states of matter, liquids have particular advantages in terms of easy handling and recycling, which has been manifested in various chemosynthetic reactions, but remains underexplored in graphene synthesis. This work reports the direct conversion of liquid organic precursor into versatile 3D graphene materials using rapid laser irradiation. The liquid precursor allows for easy fabrication of graphene with significant 3D architectures, including powders, patterned composite structures, and substrate‐free films. Taking advantage of the high compatibility of liquid precursor with a wide range of dopants, the 3D graphene can be further engineered together with various functional components, especially the high loading (≈15 wt.%) and well‐dispersed (an average diameter of less than 50 nm) high‐entropy alloy nanoparticles. Furthermore, combined with the 3D printing strategy, the rapid construction of graphene with complex and accurate 3D shapes is demonstrated via a selective in situ laser transforming (SLT) strategy. With the high structural integrity unachievable by traditional 3D printing methods, the obtained objects show an electrical conductivity of 4380 S m −1 and a compressive modulus of 31.8 MPa. The results reported in this work will open up a new way for the fabrication of functional carbon materials with customizable shapes and components. Abstract : A goal in graphene synthesis is to establish routes for preparing graphene materials from liquids instead of conventional solid or gaseous sources. This work reports the production of graphene materials with tunable composition directly from liquid precursor. A fundamentally new graphene 3D‐printing system is further developed for constructing 3D graphene materials with high structural integrity unachievable by traditional printing strategy.